The availability of purine nucleotides regulates natural competence by controlling translation of the competence activator Sxy. Issue 6 (13th May 2013) - Sinha, Sunita; Mell, Joshua; Redfield, Rosemary
Summary Many bacteria are naturally competent, able to bind and take up DNA from their extracellular environment. This DNA can serve as a significant source of nutrients, in addition to providing genetic material for recombination. The regulation of competence in several model organisms highlights the importance of this nutritional function, although it has often been overlooked. Natural competence is induced by starvation in Haemophilus influenzae, the model for competence regulation in the gamma‐proteobacteria. This induction depends on the activation of the global metabolic regulator CRP, which occurs upon depletion of phosphotransferase sugars. In this work, we show that the depletion of purine nucleotides under competence‐inducing conditions activates the CRP‐dependent competence‐specific regulator Sxy. Depletion of extra‐ or intra‐cellular purine nucleotides activates Sxy translation, while high levels inhibit it. This is modulated by the stem structure formed by sxy mRNA. The exact mechanism by which the nucleotide depletion signal is transduced is unclear, but it does not involve direct binding of purine intermediates to the sxy stem, and does not require Hfq or competence proteins. Similar regulation occurs in the relatives of H. influenzae, Actinobacillus pneumoniae and A. suis, confirming the importance of processes enabling competent bacteria to exploit the abundant DNA in their environments.